Moet ons die Belydenis van belhar (1986) as 'n nuwe Belydenisskrif aanvaar? - Van Niekerk, A. C. J. (Verbum et ecclesia, 1996)
Can we accept the Confession of Belhar (1986) as a new doctrinal confession? The possibility exists that the Dutch Refonned Church (DRC) could stop the process of church unity in its own family due to its refusal to accept The Confession 1986 (Confession of Belhar) as afourth refonned confession. In this article the question of acceptance is examined from four perspectives and it is concluded that it should be accepted if the DRC wants to gain credibility. First the nature, characteristics and history of confessions oblige the Church in difficult situations to adopt new confessions. Secondly the history of the DRC and its family makes it imperative to overcome the gulf between believers from the same tradition through the "language of confession". Thirdly the main contents of the confession is biblically sound while absolutism of different kinds is avoided. Lastly it is argued that the confession satisfies the requirement for both contextual relevance and universal applicability.